Nuevas tecnologías en levantamientos aplicadas a la restauración: “El Giraldillo’’ - José Antonio Barrera Vera; Antonio Pérez Romero; Rafael Ortiz Marín; Carlos Cobos Gutiérrez (Virtual Archaeology Review)
This work consists in the geometric survey of a big statue by means of a laser scanner and solid modelling. It has been chosen, for its complexity and singularity of the image. It’s about the copy of the weather vane that crowns the tower of the Giralda of Seville, the well-known " Giraldillo ", carried out by traditional methods a few years ago. The big dimensions of the study object and its location in a public place make that other methods of obtaining of data cannot be applied without using auxiliary elements to be carried out, this would suppose to have disable its exhibition during a certain time.